Complications of breast biopsies: a retrospective cohort study - Cunha, Amélia (2019)
Image-guided breast biopsy is an effective method for the diagnosis of breast cancer, although it has been described the occurrence of complications. Objective: To quantify the prevalence of breast biopsies complications occurred in the Breast Imaging of the Portuguese Institute of Oncology of Porto during 2017. Results: In a total of 6.9% (95%CI: 5.5%−8.6%) and 1.9% (95%CI: 1.2%−2.8%) of the 1180 breast biopsies performed occurred at least one immediate (during the procedure or until the patient leaves the service) or late (after the participant leaves the service and up to 30 days after) complications, respectively. The most frequent immediate and late complications were pain and the presence of inflammatory signs at the biopsy site, respectively. Conclusion: The complications of breast biopsies were an uncommon event, affecting 7 out of 100 participants in the immediate and about 2 out of 100 participants up to 30 days after its execution.